Xanomeline-Trospium for Adults with Schizophrenia Experiencing Acute Psychosis: A Systematic Review and Meta-analysis of Safety and Tolerability Outcomes - Kishi, Taro; Citrome, Leslie; Sakuma, Kenji; Hamanaka, Shun; Nishii, Yasufumi; Hatano, Masakazu; Furukawa, Osamu; Saito, Youichi; Iwata, Nakao (Pharmacopsychiatry, 2025)
The United States Food and Drug Administration approved the xanomeline-trospium combination in September 2024 for treating schizophrenia, based in part on three double-blind, randomized placebo-controlled trials in adults with schizophrenia experiencing acute psychosis. This random-effects model pairwise meta-analysis of those three trials found that xanomeline-trospium was comparable to placebo in terms of all-cause discontinuation, discontinuation rate due to adverse events, Simpson–Angus Scale score change, Barnes Akathisia Rating Scale score change, body weight change, body mass index change, blood pressure change, serum total cholesterol change, blood glucose change, QTc interval changes, and the incidence of headache, somnolence, insomnia, dizziness, akathisia, agitation, tachycardia, gastroesophageal reflux disease, diarrhea, increased weight, and decreased appetite. However, xanomeline-trospium was associated with a higher incidence of at least one adverse event, dry mouth, hypertension, nausea, vomiting, dyspepsia, and constipation, and increased serum triglyceride compared with placebo. Notably, xanomeline-trospium demonstrated superior efficacy than placebo in improving the Positive and Negative Syndrome Scale (PANSS) total score, PANSS positive subscale score, and PANSS negative subscale score.
Keywords: xanomeline-trospium; KarXT; schizophrenia experiencing acute psychosis; efficacy and safety; systematic review and meta-analysis